Bioactive Compounds and Antioxidant Capacity of Pulp, Peel and Seeds from Jeriva (Syagrus romanzoffiana) - Beatriz C. B. S. Mello; Angelika Malarski; Volker Böhm (MDPI AG, 2024)
Jeriva (Syagrus romanzoffiana) is a fruit from palm trees of the Arecaceae family, widely distributed in tropical and subtropical areas of Latin America. It has low production costs and high productivity throughout the year; however, its consumption is very low, and the production goes almost entirely to feed animals or to waste. To improve its consumption, a good characterization of the whole fruit is necessary. The objective of this work was to evaluate the jeriva pulp, peel and seeds according to carotenoids, phenolic compounds, vitamin C, tocopherols and antioxidant potential using HPLC, microplate readers and spectrophotometric methods. Every part of the fruit exhibited antioxidant capacity in the ORAC and TEAC tests, which can be attributed to its high concentration of polyphenols. Carotenoids were more present in the pulp and peel and almost absent in the seeds. Vitamin C ranged from 12 ± 1 for the seeds up to 92 ± 3 mg/100 g for the pulp. The total phenolic content was quantified between 473 ± 39 for the seeds and 1089 ± 32 mg of gallic acid equivalents (GAEs)/100 g for the pulp. These results demonstrate that all parts of this fruit have important bioactive nutrients, with promising perspectives for further scientific approaches and for composing formulations of food products to enhance functional properties.